Leaving Performance-Oriented Goal (Ranking) Based Education To Improve Student Learning Motivation - Rai Saba, Mahitri Wiyani; Sutarti, Titin (Jayapangus Press, 2024)
Society believes that ranking can be extrinsic motivation for students to improve learning performance, achievement, and student achievement. Ranking also makes it easier for schools to find out the quality of schools, formulate policies, and select colleges to enter. On the other hand, ranking triggers